Agronomy of ginger (Zingiber officinule Rosc.) a review - THANKAMANI, K V PETER, K KANDIANNAN, K SIVARAMAN, C K (Journal of Spices and Aromatic Crops, 1996)
Ginger (Zingiber officinale) is grown in tropical and sub-tropical regions of the world for it’s spice and medicinal values. Successful production of ginger depends on efficient use of available resources by adopting suitable agronomic practices. Such practices like land preparation, seed selection, seed rate, seed treatment, planting season, depth of planting, mulchlng, nutrient management, use of growth regulators, weed control, irrigation, shade requirement and harvest management are reviewed in detail. The review also covers climatic requirement for cultivation, soil suitablity, establishment and growth, pests and diseases, cropping systems, ratooning and economics of cultivation.